The Prosody of English Spoken with a Croatian Accent - Josipović, Višnja (Array, 1997)
The author analyses the distorted prosody of English spoken with a Croatian accent (ESCA) and points to the typological differences which have to be taken into account when explaining and predicting these distortions. The features of ESCA are established on the basis of the results of experimental research and are identified as: the wrong timing of crucial melodic peaks ; the wrong timing of crucial melodic turning points due to distorted rhythm ; the potentially wrong use of the intonational morpheme L*+H, i.e., its use for wrong pragmatic purposes ; resorting to un-English means of fulfilling the pragmatic purposes of the English prefixed patterns L+H* and H+L* ; insufficient use of rising tunes, which are then typically made up for by un-English means ; and finally, extensive use of paralinguistic prosodic means to express the meanings of intonational entities that Croatian does not have.